2015
DOI: 10.1111/jfq.12126
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Bioactive Compounds and Quality Parameters of Grugru Palm Powder (Acrocomia Aculeata) in Different Drying Conditions

Abstract: The objective of this paper was to study the stability of bioactive components of grugru palm powder. Fruits were selected, sanitized and pulped; subsequently, the pulp was crushed and submitted to the following four treatments: oven drying (T1: without maltodextrin; T2: with 8% of maltodextrin) and lyophilization (T3: without maltodextrin; T4: with 8% of maltodextrin). The powders of each treatment were packed in plastic, laminate or laminate and vacuum (LV). Analyses of the physicochemical and bioactive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
2
3
0
Order By: Relevance
“…On the other hand, the addition of gum Arabic had no clear influence on TPC retention. Similar behavior was observed by Oliveira, Lima, Clemente, Afonso, & Costa (2015) when analyzing the TPC of freeze dried grugru palm (Acrocomia aculeate) with 8% (w/v) maltodextrin during 120 days of storage.…”
Section: Color Analysessupporting
confidence: 50%
“…On the other hand, the addition of gum Arabic had no clear influence on TPC retention. Similar behavior was observed by Oliveira, Lima, Clemente, Afonso, & Costa (2015) when analyzing the TPC of freeze dried grugru palm (Acrocomia aculeate) with 8% (w/v) maltodextrin during 120 days of storage.…”
Section: Color Analysessupporting
confidence: 50%
“…Oliveira et al (2015b), in the storage of lyophilized macaúba palm, in three different types of package, observed that the laminated package with vacuum was the most effective to maintain water activity of the product, corroborating with the present study.…”
Section: Resultssupporting
confidence: 77%
“…Oliveira et al (2015b) cite the laminated package with vacuum as more efficient to maintain the yellow color in the lyophilized macaúba pulp. Lisbôa et al (2012) observed reduction greater than that of the present study, from 17 to 19% in prickly pear powder at 40 ºC, stored in laminated package.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors also reported increased moisture and water activity in powder products stored in different packaging materials during storage (Koç et al, 2011a;Oliveira et al, 2015;Udomkun et al, 2016). Seth et al (2018) reported an increase from 4.85% to almost 9% moisture (dry basis) for powdered sweetened yogurt (spray-dried), stored in LDPE package for 49 days at 38 ± 1 ºC and 90% RH.…”
Section: Period (Days)mentioning
confidence: 97%
“…Several studies have already been developed to evaluate the interference of packaging on the stability of powdered foods, such as apple peel (Henríquez et al, 2013), macaúba palm (Oliveira et al, 2015) and sweetened yogurt (Seth et al, 2018) throughout storage. Moura et al (2008) evaluated the effects of different packages on the internal quality of fresh Japanese quail eggs.…”
Section: Introductionmentioning
confidence: 99%